2018
DOI: 10.1002/elan.201700522
|View full text |Cite
|
Sign up to set email alerts
|

Development of Glass‐sealed Gold Nanoelectrodes for in vivo Detection of Dopamine in Rat Brain

Abstract: In vivo monitoring of dopamine (DA) in cerebral nervous system with no traumatic brain injury is still a challenging work for reliably evaluating the role that DA plays in physical and cognitive functionality. In this work, to reduce the traumatic injury on the brain tissue, we develop a glass‐sealed Au nanoelectrode (GSNE) with nanoscale physical dimention for cerebral DA detection. First, an Au microwire was sealed into the pre‐thinned silica capillary. Then, the obtained Au/capillary assembly was pulled int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Additionally, biosensors can only monitor one compound at a time . The most recent advancements in microelectrodes and biosensors manufacturing enabled real-time monitoring of choline, dopamine, ascorbic acid, and oxygen in brains of freely moving rats. , It is also noteworthy that new direct-to-MS-compatible technologies such as probe electrospray ionization are being adapted for in vivo brain sampling in rodents …”
mentioning
confidence: 99%
“…Additionally, biosensors can only monitor one compound at a time . The most recent advancements in microelectrodes and biosensors manufacturing enabled real-time monitoring of choline, dopamine, ascorbic acid, and oxygen in brains of freely moving rats. , It is also noteworthy that new direct-to-MS-compatible technologies such as probe electrospray ionization are being adapted for in vivo brain sampling in rodents …”
mentioning
confidence: 99%
“…The SEM images showed that a hollow quasi-disk structure of the tip was formed with a radius of 139 ± 3 nm . This proof-of-concept implantable sensor detected DA over a wide concentration range (pM to μM) in PBS, outperforming most metal-based electrochemical sensors. Although the device was not implemented for in vivo metabolite monitoring, it holds great potential due to the miniaturized form of the transistor. The needle-type format bypasses the limitations of the conventional “chip-architecture” of OECTs, allowing the sensors to be precisely positioned for single-cell analysis …”
Section: Applicationsmentioning
confidence: 99%
“…Detection of DA in the presence of ascorbic acid (AA) was studied using linear sweep voltammetry (LSV) with wafer-scale manufactured Au nanoelectrodes having 30–500 nm width [ 41 ] and using redox cycling with 150 nm width Au interdigitated electrodes (IDEs) [ 42 ], demonstrating improved analytical performances with respect to standard Au thin-film electrodes and faradaic current enhancement, respectively. An implantable 800-nm diameter Au nanotip modified with Au nanoclusters and Nafion was employed as amperometric DA sensor in the striatum of rats, where the concentration of evoked DA release was estimated to be 37 nM [ 43 ]. The analytical performance of a carbon nanopipette electrode (CNPE) with ∼250 nm tip diameter and controllable length of exposed carbon, ranging from 5 to 175 μm, was characterized for neurotransmitters detection by FSCV, demonstrating higher sensitivity in serotonin sensing than traditional CF microelectrodes [ 44 ].…”
Section: Micro- and Nano-sized Amperometric Sensorsmentioning
confidence: 99%